2004
DOI: 10.37236/1810
|View full text |Cite
|
Sign up to set email alerts
|

On-line Ramsey Theory

Abstract: The Ramsey game we consider in this paper is played on an unbounded set of vertices by two players, called Builder and Painter. In one move Builder introduces a new edge and Painter paints it red or blue. The goal of Builder is to force Painter to create a monochromatic copy of a fixed target graph $H$, keeping the constructed graph in a prescribed class ${\cal G}$. The main problem is to recognize the winner for a given pair $H,{\cal G}$. In particular, we prove that Builder has a winning strategy for any $k$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 3 publications
1
54
0
Order By: Relevance
“…. For a fixed graph H, studying the ratio of r H ( ) and R H ( ) e was initiated in [2,10,14] and has drawn much attention since then [11][12][13]20]. There is also a line of research trying to determine some exact online Ramsey numbers [5,7,8,12,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…. For a fixed graph H, studying the ratio of r H ( ) and R H ( ) e was initiated in [2,10,14] and has drawn much attention since then [11][12][13]20]. There is also a line of research trying to determine some exact online Ramsey numbers [5,7,8,12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…She showed that one direction of the conjecture is true while the other direction is not. Theorem 1.3 (Grytczuk et al [11]). Painter wins the online Ramsey game for C 3 on outerplanar graphs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall the statement of Theorem 5.Theorem 5. If H is a 3-uniform hypergraph, then τ g (H) ≤ 516 (n H + m H ). As a further consequence of Theorem 8, we have the following upper bound on the game transversal number of a 3-uniform hypergraph with maximum degree at most 2.…”
mentioning
confidence: 99%